Lexical Relationship Between Dayak Ngaju and Dayak Sampit Languages: A Lexicostatistical Study - Putri, Julie Abiya; Qalyubi, Imam (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2025)
This study investigates the lexical relationship between Dayak Ngaju and Dayak Sampit languages in Central Kalimantan using a lexicostatistical approach. A 200-item Swadesh list was used to compare basic vocabulary obtained from a bilingual speaker fluent in both languages. The data were analyzed by identifying cognate pairs and calculating the percentage of shared vocabulary. The findings reveal that 155 out of 200 words (77.5%) are cognates, indicating a strong lexical relationship. This percentage places the two languages within the same language family based on commonly used classification thresholds in lexicostatistics. The analysis further categorizes the cognates into four types: identical forms, regular phonemic correspondences, phonetically similar pairs, and pairs with one phoneme difference. These results provide evidence of a close historical and linguistic connection between the two languages and contribute to the understanding of language variation and development among the Dayak languages in Indonesia.